Evaluation and identification of powdery mildew-resistant genes in 137 wheat relatives - Wang, Jiaojiao; Xu, Hongxing; Qie, Yanmin; Han, Ran; Sun, Xiaohui; Zhao, Ya; Xiao, Bei; Qian, Zejun; Huang, Xiaomei; Liu, Ruishan; Zhang, Jiadong; Liu, Cheng; et al. (Frontiers in Genetics, 2024)
Powdery mildew is one of the most severe diseases to common wheat yield and quality, which is caused by Blumeria graminis f. sp. tritici (Bgt). Host resistance is preferred strategy to prevent this disease. However, narrow genetic basis of common wheat expanded the demand for diversified germplasm resources against powdery mildew. Wheat relatives, especially the secondary gene pool of common wheat is important gene donors in the genetic improvement of common wheat as its abundant genetic variation and close kinship with wheat. In the present study, a series of 137 wheat relatives, including 53 Triticum monococcum L. (2n = 2x = 14, AA), 6 Triticum urartu Thumanjan ex Gandilyan (2n = 2x = 14, AA), 9 Triticum timopheevii Zhuk. (2n = 4x = 28, AAGG), 66 Triticum aestivum subsp. Spelta (2n = 6x = 42, AABBDD) and 3 Aegilops speltoides (2n = 2x = 14, SS), were systematically evaluated their powdery mildew resistance and composition of Pm genes. 83 out of 137 (60.58%) accessions were resistant to Bgt isolate E09 at the seedling stage, and 116 of 137 (84.67%) wheat relatives were resistant to the mixture of Bgt isolates at the adult stage, indicating these accessions showed a high level of resistance to powdery mildew. Then, 31 markers for 23 known Pm genes were used to test these 137 accessions, the results showed that only Pm2, Pm4, Pm6, Pm58 and Pm68 were detected. Among them, three Pm4 alleles (Pm4a, Pm4b and Pm4f) were identified in four T. subsp. Spelta accessions. q-RT PCR further confirmed that Pm4 alleles played a role in disease resistance in these four accessions. The phylogenetic tree showed that the kinship of Pm4 was closed to Pm24 and Sr62. This study not only provided reference information and valuable germplasm resources for breeding of new wheat varieties with disease resistance, but laid the foundation for enriching the genetic basis of wheat powdery mildew resistance.